1994
DOI: 10.1088/0953-4075/27/22/004
|View full text |Cite
|
Sign up to set email alerts
|

Features of the differential cross section in the 2s-3s excitation of the hydrogen atom by electron and positron impact

Abstract: Differential cross sections for the 2s-3s excitation of hydrogen atoms by electron and positron impact are reported at two incident energies, 10 eV and 50 eV, using a distorted wave method based on the two potential model. Dramatic differences between the electron and positron results are noticed at both energies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 10 publications
2
18
2
Order By: Relevance
“…Full optical potential (continuum optical potential plus positronium formation optical potential) (solid), continuum optical potential only (dotted) and pure close coupling (dashed) results are presented in (a). A comparison between the present CCOB results (solid), the results of Jha et al [8] (dashed), Deb et al [9] (dash dotted) and Kulhar [11] (dotted) is shown in (b). can be seen in figures 2(a) and 3(a), the effects of optical potentials become weak as the incident energy increases and they only cause a slight difference in the magnitude of cross sections.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…Full optical potential (continuum optical potential plus positronium formation optical potential) (solid), continuum optical potential only (dotted) and pure close coupling (dashed) results are presented in (a). A comparison between the present CCOB results (solid), the results of Jha et al [8] (dashed), Deb et al [9] (dash dotted) and Kulhar [11] (dotted) is shown in (b). can be seen in figures 2(a) and 3(a), the effects of optical potentials become weak as the incident energy increases and they only cause a slight difference in the magnitude of cross sections.…”
Section: Resultsmentioning
confidence: 74%
“…From figures 1(b) and 3(b) we see great disagreement among these curves obtained with different theoretical models at intermediate and large scattering angular regions. The results of Jha et al [8] showed sharp dips in the curves of the differential cross section for both energies, while Kulhar [11] obtained shallow minima at different scattering angles. There was no dip in the results of Deb et al [9] and Ghoshal and Mandal [10].…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Using their high resolution trapped positron source, they studied vibrational and electronic excitation of H 2 , N 2 , CH 4 and Ar and found comparable cross sections for positron and electron impact in the threshold region. Theories, on the other hand, predict differences in the total and differential cross sections (Walters 1988, Jha 1994, Lino et al 1994. Indirect information about projectile excitation in Ps-atom collisions was obtained by Szluińska et al (2002b) but, overall this area will probably stay mostly unexplored until more intensive positron beams become commonly available.…”
Section: Excitation Studiesmentioning
confidence: 99%